Insert the corresponding expression:
(4×6)b=
To solve this problem, we will follow these steps:
- Identify the given expression: (4×6)b.
- Apply the power of a product rule: (a×b)n=an×bn.
- Separate the expression by distributing the exponent to both elements in the product.
Now, let us apply these steps:
The expression we start with is (4×6)b. According to the power of a product rule, (a×b)n=an×bn, we distribute the exponent b to each base:
(4×6)b=4b×6b.
Therefore, the expression (4×6)b can be rewritten as 4b×6b, which corresponds to choice 1.